Research and the police in South Africa: the case of a violent, unequal, post-authoritarian democracy - Faull, Andrew (Introduction to policing research, 2024)
This chapter offers insight into the nature, experience and impact of police-related research in South Africa, a demographically diverse, upper-middle-income democracy characterised by extreme inequality and violent crime. It is a post-authoritarian state struggling to reform its police while grappling with an oppressive past. The pressure to decolonise and democratise knowledge, and question how and by whom it is created, remain prescient. But it is also a country where fear of crime saturates daily life, fuelling a largely unmet expectation that police will bring safety. Against this background, research on South African police has a long, if not consistently impactful, history. Taking this into account, this chapter highlights the importance of context in police research and explores the practicalities, ethics and impact of research on and with police in South Africa.